The relationship between psychological compatibility and academic achievement in swimming - Al Dababseh, M. F.; Mousa Ay, K. M.; Abu Altaieb, M. H.; Hammouri, W. Y.; Abu Areeda, F. S. (Journal of Human Sport & Exercise, 2017)
This study aims to determine the relationship between psychological compatibility and academic achievement in swimming class, the subjects were (72) under graduate male students of physical education college at the University of Jordan. (M age = 19.4 SD =1.35). All subjects were students in swimming class and they were learning free style swimming skills. The learning scores for students were measured two times during the second semester in 2016; the subjects went through practical exams only, the med-term exam (30) grades, and the final-term exam (30) grades, the total grades score was out of (60). The researchers designed a questionnaire as a tool for this study to measures the degree of psychological compatibility for the subjects. The total scores for learning free style swimming skills and the scores for the questionnaire were compared to determine the relationship between psychological compatibility and academic achievement in free style swimming, Statistical treatment by using the (SPSS) program was done. The results showed that there was a relation between psychological compatibility and academic achievement during learning free style swimming skills.